The Determinants of Cash Conversion Cycle and Firm Performance: An Empirical Research for Borsa Istanbul Turkey - Mesut Doğan; Mustafa Kevser (Management and Economics Review, 2020)
The ultimate goal of firms is to make a profit and to achieve this ultimate goal, firms execute various functions. Finance is one of the basic functions of firms and firms need financial instruments such as cash reserve and outsource to carry out their activities. Cash management within the finance function is an important issue that needs to be carefully considered, especially in the short and medium term financial planning stage. Presently, the high competition among firms forces companies to manage their cash in the most effective way. The conceptual studies on the subject are quite old and date back to Keynes. According to Keynes, firms demand cash for transaction, prudence and speculation. As a result of analysis, it has been determined that cash conversion cycle has an impact on return on assets (ROA) and return on equity (ROE). There is a statistically significant and negative relationship between cash conversion cycle (CCC) return on assets (ROA) and return on equity (ROE). In addition, there is a positive relationship between return on assets (ROA) and firm size while there is a negative and statistically significant relationship between debt ratio (DEBT) and return on assets (ROA).
Keywords: L10; M21; 330; cash flow; cash conversion cycle; firm performance; industrial index